Abreviation Establishment in Instagram Social Media - Verlin, Sri (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study aims to describe the process of forming abbreviations used on Instagram. The method used in this study is observation by taking screenshots and recording abbreviation data. Furthermore, the sample used in this study does not depend on quantity but rather on quality based on the range and depth of the problems studied. The results of this study indicate that the process of forming abbreviations still follows the old pattern, and the new pattern is in the form of only one abbreviation, each retaining the first letter of each component and retaining the first letter with a number. Furthermore, abbreviations that still follow the old pattern and the new pattern in the form of acronyms consist of three respective formation processes, namely the preservation of the first letter of each component, the preservation of the first syllable of each component, the preservation of the first syllable and the preservation of the first letter of each component, and the preservation of the first syllable of the first word and the last syllable of the last word. The various syllables and letters of some components are conserved by the omission of prepositions, and the various syllables and letters of some components are conserved by omission. The second and third patterns are the dominant new patterns used in Instagram social media. The dominant use only pays attention to sound so that it looks slangy and pleasing to the listener's ear without paying attention to its logic.